Deviant Calvinism : broadening Reformed theology - Crisp, Oliver (2014)
Deviant Calvinism seeks to show that the Reformed tradition is much broader and more variegated than is often thought. Crisp's work focuses on a cluster of theological issues concerning the scope of salvation and shows that there are important ways in which current theological discussion of these topics can be usefully resourced by attention to theologians of the past.
Tradition, Faith, and Doctrine -- Eternal Justification -- Libertarian Calvinism -- Augustinian Universalism -- Universalism and Particularism -- Barthian Universalism? -- Hypothetical Universalism -- The Double-Payment Object.
Includes bibliographical references (pages 241-253) and index.
Keywords: Calvinism -- History of doctrines